Relationship Between the Cultivation and Incentive Mechanism of Senior Educational Talents - Jialin Zuo (Kassel University Press, 2021)
The attraction and mobility of senior educational talents hinge on the talent cultivation and incentive mechanism of various enterprises. If the mechanism is imperfect, the talents will be less active and creative in work, and the enterprises will underperform in the long term. This paper combines literature review, questionnaire survey, and mathematical analysis to summarize the current situation of the cultivation and incentive mechanism of senior educational talents in an enterprise in a region, and analyze the defects of the existing mechanism. The results show that: the senior educational talents have not received sufficient compensations or incentive measures; the employees do not have a smooth promotion channel; the enterprise fails to issue clear and innovative reward policies. To address these defects, this paper proposes improvement measures and optimization schemes: To boost the enthusiasm and creativity of employees in work, the enterprises should give full play to the personal values of senior educational talents, strive to introduce more excellent talents, and establish a sound salary distribution system and reasonable promotion polices. The research results lay a theoretical basis for enterprises to cultivate and absorb the necessary senior educational talents.